Impact of Epithelial–Stromal Interactions on Peritumoral Fibroblasts in Ductal Carcinoma in Situ. (28th February 2019) - Strell, Carina; Paulsson, Janna; Jin, Shao-Bo; Tobin, Nicholas P; Mezheyeuski, Artur; Roswall, Pernilla; Mutgan, Ceren; Mitsios, Nicholas; Johansson, Hemming; Wickberg, Sarah Marie; Svedlund, Jessica; Nilsson, Mats; et al.
Abstract: Background: A better definition of biomarkers and biological processes related to local recurrence and disease progression is highly warranted for ductal breast carcinoma in situ (DCIS). Stromal–epithelial interactions are likely of major importance for the biological, clinical, and pathological distinctions between high- and low-risk DCIS cases. Methods: Stromal platelet derived growth factor receptor (PDGFR) was immunohistochemically assessed in two DCIS patient cohorts (n = 458 and n = 80). Cox proportional hazards models were used to calculate the hazard ratios of recurrence. The molecular mechanisms regulating stromal PDGFR expression were investigated in experimental in vitro co-culture systems of DCIS cells and fibroblasts and analyzed using immunoblot and quantitative real-time PCR. Knock-out of JAG1 in DCIS cells and NOTCH2 in fibroblasts was obtained through CRISPR/Cas9. Experimental data were validated by mammary fat pad injection of DCIS and DCIS- JAG1 knock-out cells (10 mice per group). All statistical tests were two-sided. Results: PDGFRα (low) /PDGFRβ (high) fibroblasts were associated with increased risk for recurrence in DCIS (univariate hazard ratio = 1.59, 95% confidence interval [CI] = 1.02 to 2.46; P  = .04 Wald test; multivariable hazard ratio = 1.78, 95% CI = 1.07 to 2.97; P  = .03). Tissue culture and mouse model studies indicated that this fibroblast phenotype is induced by DCIS cells in a cell contact-dependent manner. Epithelial Jagged1 and fibroblast Notch2 were identified through loss-of-function studies as key juxtacrine signaling components driving the formation of the poor prognosis-associated fibroblast phenotype. Conclusions: A PDGFRα (low) /PDGFRβ (high) fibroblast subset was identified as a marker for high-risk DCIS. The Jagged-1/Notch2/PDGFR stroma–epithelial pathway was described as a novel signaling mechanism regulating this poor prognosis-associated fibroblast subset. In general terms, the study highlights epithelial–stromal crosstalk in DCIS and contributes to ongoing efforts to define clinically relevant fibroblast subsets and their etiology.